Knowledge and Implementation of Infection Control Measures Among Nurses Caring for Patients with Chemical Gas Exposure - Rutvi (International Journal of Emergency and Trauma Nursing and Practices, 2025)
The purpose of this study was to evaluate the level of knowledge and the extent of implementation of infection control measures among nurses caring for patients exposed to chemical gases. A descriptive cross-sectional design was adopted, and a sample of staff nurses working in clinical settings with potential chemical exposure roles was selected using convenience sampling. Data were collected via a structured questionnaire assessing knowledge of chemical inhalation hazards and infection control practices, and via an observational checklist to measure real-time adherence to protective protocols. The findings revealed that while many nurses demonstrated basic awareness of the risks associated with inhaled toxic gases and standard infection control procedures, significant gaps remained in their understanding of targeted decontamination routines, personal protective equipment (PPE) selection, and airborne transmission mitigation. Observational data indicated that implementation of key protocols, such as proper donning and doffing of PPE, timely environmental ventilation, and chemical spill decontamination, was inconsistent. A positive correlation emerged between knowledge scores and practice compliance, indicating that higher levels of knowledge were associated with better implementation of infection control measures. These findings highlight the need for enhanced educational initiatives, periodic drills, and institutional policies that support the safe management of patients with chemical gas exposure. Strengthening both theoretical understanding and practical skills among nursing professionals is vital for safeguarding patient outcomes and ensuring workplace safety in scenarios involving inhalation of hazardous gases.
Keywords: Chemical gas exposure; nursing knowledge, infection control practices, personal protective equipment, environmental decontamination